2022
DOI: 10.3390/nu14153134
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Aging and Metabolic Disorder, and the Impact of Nutritional Interventions

Abstract: Adipose tissue is the largest and most active endocrine organ, involved in regulating energy balance, glucose and lipid homeostasis and immune function. Adipose tissue aging processes are associated with brown adipose tissue whitening, white adipose tissue redistribution and ectopic deposition, resulting in an increase in age-related inflammatory factors, which then trigger a variety of metabolic syndromes, including diabetes and hyperlipidemia. Metabolic syndrome, in turn, is associated with increased inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…In this regard, it is interesting to note that our research indicated the importance of RXFP3 in glucometabolic activity [127][128][129][130], while GPR19 has been more strongly associated with lipid metabolism [131,132]. In this respect, perhaps simplistically, RXFP3 and GPR19 may function as "yin and yang" in the realm of the balance between glucose or lipid metabolic functionality [18,23,[133][134][135][136]. Thus, it may be likely that GPCR systems could possess a nuanced level of interaction between the multiple stress-related factors that control molecular aging [33].…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, it is interesting to note that our research indicated the importance of RXFP3 in glucometabolic activity [127][128][129][130], while GPR19 has been more strongly associated with lipid metabolism [131,132]. In this respect, perhaps simplistically, RXFP3 and GPR19 may function as "yin and yang" in the realm of the balance between glucose or lipid metabolic functionality [18,23,[133][134][135][136]. Thus, it may be likely that GPCR systems could possess a nuanced level of interaction between the multiple stress-related factors that control molecular aging [33].…”
Section: Discussionmentioning
confidence: 76%
“…The findings of the present study showed that fat pad weights increased due to continuous consumption of sugar solution. It seems that visceral white adipose tissue depots such as mesenteric uptake the Glucose for use in triacylglycerides (TAG) production (25,26). It is well established, along with obesity, that the WAT presents an increase in inflammatory markers and infiltration of immune cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Some vitamins also possess substantial anti-obesity potential [ 6 , 129 ]. The antioxidant and hepatoprotective activity of tocopherol helps in preventing metabolic syndrome [ 130 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%